Nostalgic advertisements in multicultural Malaysia: a multimodal analysis - Melissa Shamini Periasamy; Ganakumaran Subramaniam; Gruba, Paul (Penerbit Universiti Kebangsaan Malaysia, 2017)
Advertisements that feature nostalgia as a theme have been highly successful in their ability to evoke an emotional reaction in consumers thus connecting them to the brand and product being advertised. Nostalgic advertisements are memorable as they prompt consumers to draw from their own past experiences in a positive manner therefore creating a “feel good” factor in consumers. Nostalgia has been a popular theme in many Malaysian television commercials (TVCs) in the past decade. This study examines a Malaysian national day TVC using a thematic multimodal approach to analyse how nostalgia is reinforced through the multimodal elements in the TVC. The analysis includes a discussion of the types of nostalgia elicited by the multimodal elements in the TVC in reference to the socio-cultural context of multicultural Malaysia. The findings reveal how specific multimodal elements in the TVC are used to evoke a sense of collective nostalgia among Malaysians of diverse socio-cultural backgrounds. This study shows that personal, collective, historical or national nostalgia is reinforced in a Malaysian national day TVC by making references to dates, events, images, relationships and values that are significant and meaningful to all Malaysians regardless of ethnicity, religion or belief. Such advertisements serve to transcend ethnic and religious boundaries to create a national mindset that the whole nation can connect with instead of communal or ethnic based ones.